RELATIONSHIP BETWEEN PSYCHOLOGICAL INFLEXIBILITY, DEPRESSION AND AGGRESSION - Nadiradze, Eka; Lodia , Teona (Georgian Psychological Journal, 2022)
Psychological inﬂexibility, which is the fundamental component of acceptance and commitment therapy, is considered as one of the main aspects of psychopathologies. The given work aims to deter- mine relationship between psychological inﬂexibility and maladaptive conditions, such as depression and aggression. The research was carried out on Georgian population and involved 157 adolescents 14-16 years of age, from Georgian public schools. 81 of them where male, and 76 were female. Corre- lation analysis showed strong positive correlation between depression and psychological inﬂexibility (r=.68) in all age groups. Strong positive correlation was revealed between aggression and psycho- logical inﬂexibility (r=.59). Furthermore, psychological inﬂexibility is kind of a mediator in the rela- tionship of depression and aggression. Detecting the associations between psychological inﬂexibility, aggression and depression will allow to determine the basic aspects of maladaptive conditions, and by the implementation of therapy methods, help adolescents to overcome emotional dysregulations.